Geochemical dynamics and bioavailability of iodine and selenium - Ahmad, Saeed (2020)
Iodine (I) and selenium (Se) are vital dietary micronutrients for human and animal health. Approximately 35% of the world population is living at risk of I deficiency and more than half a billion people worldwide are thought to be facing Se deficiency. Historically, I deficiency has been reported in Gilgit-Baltistan (GB), Pakistan. The deficiencies of both I and Se are dietary and people of GB are largely consuming locally grown agricultural produce. Soil characteristics control the availability of I and Se to plants. Therefore, better understanding of I and Se geochemistry is required to enhance the dietary intake of these essential micronutrients via the food chain.